Perencanaan Persediaan Bahan Baku Semen Menggunakan Pendekatan Min-Max Inventory Berbasis Peramalan - Najmadan Febriawan; Famila Dwi Winati; Karina Amanda Larasati (Journal of Industrial and Mechanical Engineering, 2025)
PT Solusi Bangun Indonesia is a cement manufacturing company that utilizes FABA (Fly Ash and Bottom Ash) as one of its supplementary raw materials. A significant issue faced by the company is the overstock of FABA, which contributes to increased storage costs and poses a risk of environmental pollution. This research aims to develop an optimal inventory planning strategy for FABA by integrating time series forecasting methods with a min-max inventory control policy. The study utilizes historical FABA demand data from July 2023 to June 2024. Three forecasting techniques are applied: moving average, weighted moving average, and exponential smoothing. Accuracy evaluation indicates that the moving average method with a parameter of n = 3 produces the lowest forecasting error, as measured by MSE and MAD. The forecasting model is further validated using the Moving Range Chart to ensure its stability and reliability. The calculated safety stock at a 95% service level is 191.34 tons, with a minimum inventory of 758.83 tons and a maximum of 1,326.31 tons. This forecasting-based min-max policy effectively enhances inventory efficiency, mitigates risks of overstock and stockout, and supports operational sustainability.